Performa motor bakar silinder tunggal dengan variasi angka oktan bahan bakar dan tekanan kompresi - B. Rahmat; M.B.R. Wijaya; Y.B. Wirawan; F.Z. Bahtiar (Dinamika Teknik Mesin, 2024)
In recent times, automobile and motorcycle manufacturers have been focusing on producing powerful and efficient engines. These engines are designed with high compression pressure to achieve better performance and fuel economy when using gasoline. However, it's not widely known that high-compression engines require gasoline with a high octane number. The purpose of this study was to investigate the impact of different compression pressures on the power and torsion output of a single-cylinder combustion engine, using RON 92, RON 95 and RON 100 gasoline. To modify the compression pressure, different numbers of gaskets are used on the cylinder head. Each with a quantity of 1 gasket, 2 gaskets, and 3 gaskets. This is done to manipulate the combustion chamber volume of the motorcycle engine, resulting in changes in the compression pressure values. The researchers conducted dynamometer tests to measure the performance differences, including power and torque output. The findings revealed that the engine with the highest compression pressure (11.8 kg/cm2), fueled with Pertamax racing gasoline (RON 100), delivered the highest power output of 7.8 kW, with the highest torsion output of 10 Nm. On the other hand, the engine with the lowest compression pressure (10 kg/cm2), fueled with Pertamax gasoline (RON 92), produced the lowest power output of 4.2 kW, with the lowest torsion output of 3.8 Nm.